«Here we admire everything improved»: flattery, identity and corruption in Arequipa (18th century) - Sánchez Martínez, César Félix (Mercurio Peruano, 2018)
In the middle of the 18th century, the opening of Santa Rosa monastery is an auspicious occasion for Arequipa to produce a large number of poetic compositions that exalt the virtues of the city, while hiding the dark control of the power that the mayor of the city plots with special cynicism. The travelers give news that reflect the complex scenario: the modern and orderly city that Jorge Juan and Ulloa believe to find at the beginning of the 1740s, is the same where impunity still reigns before the serious crimes committed by Mayor Jiménez Lancho, in one dimension not at all different from the serious abuses and corruption that both travelers observed in different parts of the kingdom. Both aspects were, as we know, real: on the one hand the thriving and new city and on the other the expansion of the abuses.